Correlation Between Body Mass Index Waist Hip Ratio and Body Fat Percentage with Blood Pressure in Sedentary Females Sedentary Lifestyle and Body Mass Index Alter Blood Pressure - Zia Ul Mustafa, Hassan Mahmood, Touseef, Jamshad Latif, Muhammad Aleem Uddin, Faiza Irshad, Mufassar Nishat (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The adoption of a sedentary lifestyle is a major contributor to the development of disease as well as to morbidity and mortality rates. People who have high blood pressure can benefit from regular physical activity since it lowers their blood pressure. A lower body fat percentage is connected with a lower risk of developing high blood pressure when engaging in physical activity. There is a clear correlation between the body mass index (BMI) and the percentage of body fat (BF%) in terms of the resting rate of sympathetic nerve discharge to skeletal muscle. A greater proportion of fat stored in the abdomen, as opposed to the gluteal region, is associated with an increased risk of a variety of health problems, including diabetes and cardiovascular disease. As a result, the waist-to-hip ratio should be determined in order to conduct an analysis of fat distribution that is separate from an assessment of total obesity. The materials and procedures: Random selection was used to choose from the general population one hundred healthy sedentary volunteers and one hundred healthy non-sedentary subjects. Subjects in the age group (22-55 years) who had a BMI that was greater than 30 (kg/m2) were considered to be obese. Non-obese subjects were defined as having a body mass index (BMI) between 17.50 and 25.20 kg/m2 and an age range of 22 to 55 years. The purpose of this study was to investigate the differences between healthy sedentary and non-sedentary individuals in terms of parameters such as body mass index (BMI), waist-to-hip ratio (WHR), and body fat percentage (BF%). The participants ranged in age from 22 to 55 years old, and the correlation between these parameters and blood pressure was determined. Results: The findings showed that sedentary subjects had higher levels of body mass index, waist circumference, and body fat percentage than non-sedentary subjects did, and there was a positive link between these parameters and blood pressure. Conclusion: The conclusion is that a sedentary lifestyle is linked to an increase in Body Mass Index, Waist Hip Ratio, Blood Pressure, as well as Body fat percentage and fat mass. There was a link between BMI, WHR, BF%, and FM and blood pressure that was in the positive. Keywords: Body fat; body mass index; sedentary lifestyle; waist-hip ratio